Covid-19 After Effect: School-Age Visual Acuity Analysis with Secondary Data - Kristiawan, Ayik Sudiat; Wulandari, Ratna Dwi (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Students' ability to see clearly is crucial for learning and helps them achieve more. Normal visual acuity enables students to read the writing on the blackboard clearly, which improves their comprehension of the information the teacher is providing. With the online learning system, students spend more time using a computer or phone, which impairs their visual acuity, hinders their understanding of the material, and lowers their academic performance. The purpose of this study was to ascertain how online learning affected elementary school students' visual acuity. A Snellen chart and a questionnaire are used in this observational analytic research study with a cross-sectional design. 728 students from 7 elementary schools in Surabaya's Jeruk and Lakarsantri Districts made up the sample size. The results of the study showed that 184 of the 728 students who took part had deteriorated visual acuity during the observation period. These were divided into three categories: mild (166 cases), moderate (4 cases), and severe (14 cases). 79 pupils had recently seen a level increase in their eyesight, 27 had recently experienced a level increase in their vision, and 4 had experienced an additional level gain in their vision. There is a substantial difference in visual acuity between the pre- and post-online learning periods, according to the Wilcoxon signed-rank test results. The results of this study can support responsible use of computers and mobile devices by parents, educators, and students.Keywords: visual acuity, online learning, snellen chart